Crystal polymorphism of 8OCB liquid crystal consisting of strongly polar rod-like molecules. Issue 9 (26th January 2021) - Ghosh, Subhadip; Roy, Arun
Abstract : The studies on crystal polymorphism of 8OCB liquid crystal showing a metastable PP phase and a heterogeneous CP phase as the stable ground state. Abstract : We report detailed experimental studies on the different crystal polymorphs of 8OCB (4′-octyloxy-4-cyanobiphenyl) obtained by cooling the sample from its melt. The 8OCB liquid crystal has a stable crystal phase which is known as commercial powder (CP) phase. In addition, it also exhibits various metastable crystal phases such as square-plate, needle phase and long parallelepiped (PP) phase. We identify the metastable crystal state often found on cooling the sample from its melt as PP phase which transforms to stable CP phase on aging at room temperature or by heating it above 312 K. Based on our experimental results, we find that the stable CP crystal phase of 8OCB is not a single homogeneous phase but is the coexistence of fibrillar nano-crystallites embedded in an amorphous phase. The heterogeneous nature of its stable crystal state is an intriguing feature of this pure compound consisting of relatively small rod-like molecules with a strong dipole moment along their long axis.